Comparative Analysis of a Low-Voltage CHB Inverter Without PWM and Two-Level IGBT/SiC Inverters for Electric Vehicles on Driving Cycles - Gael Pongnot; Anatole Desreveaux; Clement Mayet; Denis Labrousse; Francis Roy (IEEE Open Journal of Vehicular Technology)
Electric Vehicles (EVs) based on Cascaded H Bridge (CHB) promise reduced consumption and improved modularity, repairability, resilience, and versatility. This study focuses on evaluating the efficiency of CHB inverters utilizing low-voltage Si MOSFETs to improve EV performance and range. Through a comprehensive system-level approach and modeling, a simulation of the CHB-based powertrain is developed and experimentally validated. Electrical and mechanical simulations are conducted separately and finally combined to streamline computation times. Subsequently, CHB-based EV is compared with standard two-level inverters (2LI) across different driving cycles, considering multiple sources of losses from the battery to the road. Despite increased battery losses, CHB proves reduction of consumption during urban driving cycles, making it a compelling choice for sustainable commuter vehicles.